Proposal thermal radiation calculation using software to select equipment to be cooled in case of fire in LPG storage parks (Research, Society and Development, 2020)
Industrially, liquefied petroleum gas (LPG) is stored in spherical or cylindrical vessels, which follow strict standards in their construction in order to avoid major accidents, that may be caused by fires and explosions in neighboring equipment, and its main propagator is heat transfer by thermal radiation. If an accident occurs, to prevent further damage, a fire fighting system must be installed. When dimensioning these systems, standards and requirements are followed which indicate prescriptive criteria (fixed distances independents from the storage park conditions) for the selection of equipment to be cooled in case of fire. In order to propose the calculation of thermal radiation impact by using a software and subsequent selection of equipment to be cooled in case of fire in a LPG storage park, a case study was elaborated in this present paper, comparing the indicated in Brazilian and international standards and what was found through simulation. The quantitative research method, descriptive and analytical, was used as data acquisition techniques, bibliographic research, case study analysis and computational tools, using a computer and the ALOHA software as materials. Simulations for different sphere filling and climatic conditions were accomplished, with results that are lower than those proposed in Brazilian standards, and therefore less conservative. The simulation of the thermal radiation radius makes the assessment more reliable considering the conditions to which the LPG spheres are exposed, helping in the most correct dimensioning of the fire fighting network. Therefore, it is concluded that Brazilian standards are more conservative and obsolete in view of the advances in Fire Engineering.